Power and Influence in the Pacific Islands: Understanding Statecraftiness - Joanne Wallis; Henrietta McNeill; Michael Rose; Alan Tidwell (Routledge, 2025)
This book outlines an analytical framework to understand power, influence, and statecraft in the Pacific Islands region. With contributions by scholars from the United States, Australia, China, New Zealand, and across the Pacific Islands region, it provides 'both sides of the story' of statecraft and explores how power and influence are being exercised in the Pacific Islands. Amid escalating strategic competition, the United States, China, Australia, and a range of other partners are trying to exercise power and influence in their Pacific Islands region through their statecraft. But which partners are doing what, where are they doing it, and how are Pacific Island countries and people responding? Through case studies of key examples – such as economic assistance, defence diplomacy, scholarships, and strategic narratives – this book analyses how tools of statecraft are being deployed by a range of key partners and Pacific Island states, and how they are being received by Pacific Island countries and people. A vital resource for scholars and practitioners in International Relations and diplomacy as well as those seeking to understand how statecraft, power, and influence are being exercised in the Pacific Islands region. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.
Keywords: 300; Statecraft; Power; Influence; Strategic narratives; Geopolitics; Pacific Islands